Effect of annealing temperatures on the properties of CdZrS nanoparticles prepared by sol-gel synthesis method - A.U. Yimamu; V.N. Adoons; R.A. Phokojoe (Heliyon)
Cadmium zirconium sulphide (CdZrS) nanoparticles (NPs) were prepared using a sol-gel method. The effect of different annealing temperatures on the structural, morphological, optical, and compositional properties of CdZrS NPs was investigated. The structural investigation revealed that the CdZrS samples exhibit hexagonal and cubic structures in both the as-prepared and annealed samples. The crystallite sizes of CdZrS nanoparticles decreased with increasing annealing temperature. The scanning electron microscopy (SEM) images showed a highly agglomerated particle at 500oC. Energy dispersive X-ray spectroscopy (EDS) confirmed the presence of Cd, Zr and S in all samples. UV–Vis analysis confirmed a red shift from 2.61 to 1.62 eV when the annealing temperature was increased. Photoluminescence (PL) emission spectra showed a peak at 462 nm attributed to excitonic recombination of CdZrS and a peak at 557 nm corresponding to interstitial sulfur sites. These materials have potential applications for biosensors or solar cells technology.